Detailed molecular characterization of a novel IDS exonic mutation associated with multiple pseudoexon activation - Grodecká, L; Kováčová, T; Kramárek, M; Seneca, S; Stouffs, K; De Laet, C; Majer, F; Kršjaková, T; Hujová, P; Hrnčířová, K; Souček, P; Lissens, W; et al. (Journal of molecular medicine (Berlin, Germany), 2017)
UNLABELLED: Mutations affecting splicing underlie the development of many human genetic diseases, but rather rarely through mechanisms of pseudoexon activation. Here, we describe a novel c.1092T>A mutation in the iduronate-2-sulfatase (IDS) gene detected in a patient with significantly decreased IDS activity and a clinical diagnosis of mild mucopolysaccharidosis II form. The mutation created an exonic de novo acceptor splice site and resulted in a complex splicing pattern with multiple pseudoexon activation in the patient's fibroblasts. Using an extensive series of minigene splicing experiments, we showed that the competition itself between the de novo and authentic splice site led to the bypass of the authentic one. This event then resulted in activation of several cryptic acceptor and donor sites in the upstream intron. As this was an unexpected and previously unreported mechanism of aberrant pseudoexon inclusion, we systematically analysed and disproved that the patient's mutation induced any relevant change in surrounding splicing regulatory elements. Interestingly, all pseudoexons included in the mature transcripts overlapped with the IDS alternative terminal exon 7b suggesting that this sequence represents a key element in the IDS pre-mRNA architecture. These findings extend the spectrum of mechanisms enabling pseudoexon activation and underscore the complexity of mutation-induced splicing aberrations. KEY MESSAGE: Novel exonic IDS gene mutation leads to a complex splicing pattern. Mutation activates multiple pseudoexons through a previously unreported mechanism. Multiple cryptic splice site (ss) activation results from a bypass of authentic ss. Authentic ss bypass is due to a competition between de novo and authentic ss.
Keywords: glykoproteiny; mutace; sestřih RNA; RNA Splicing; mukopolysacharidóza II; introny; Adolescent; lidé; Introns; Glycoproteins; messenger RNA; Mutation; RNA, Messenger; RNA Splice Sites; Male; Point Mutation; Exons; bodová mutace; Splice site competition; exony; Mucopolysaccharidosis II; Complex splicing aberration; IDS; mužské pohlaví; Pseudoexon; De novo splice site; místa sestřihu RNA; mladiství; Humans